(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
As technologies become more and more pervasive in our everyday life new questions arise, for example, about security, accountability, fairness and ethics. These concerns are about all the realities that are involved or committed in designing, implementing, deploying and using the technology. This document addresses such concerns by presenting a set of practical obligations and recommendations for the development of applications and systems based on Artificial Intelligence (AI) techniques. These are derived from a definition of rights resulting from principles and ethical values rooted in the foundational charters of our social organization.